The Effectiveness of Cryptocurrency as a Hedging Tool for Capital Market Indices in Indonesia - Denis Christian; Sarwo Edy Handoyo (Green Publisher Indonesia, 2025)
This study investigates the effectiveness of cryptocurrency, specifically Bitcoin, as a hedging tool against the Indonesian stock market index (LQ-45) during periods of economic uncertainty, particularly influenced by the COVID-19 pandemic. Utilizing a dataset spanning from January 2015 to December 2024, the research employs K-Means clustering to classify periods into normal and crisis phases based on macroeconomic indicators. The DCC-GARCH model is then applied to assess the dynamic correlations between Bitcoin, the S&P 500, and gold with the LQ-45 index. Findings reveal that Bitcoin serves as both a hedging and safe-haven asset during crises, with an effectiveness of 36.61% in protecting portfolios. Conversely, the S&P 500 and gold exhibit limited effectiveness as hedging tools and do not function as safe havens during market turmoil. This study contributes to the understanding of alternative investment strategies in managing risk within emerging markets.